Biological surface-active compounds from marine bacteria. Issue 9 (2nd May 2016) - Dang, Nga Phuong; Landfald, Bjarne; Willassen, Nils Peder
ABSTRACT: Surface-active compounds (SACs) are widely used in different industries as well as in many daily consumption products. However, with the increasing concern for their environmental acceptability, attention has turned towards biological SACs which are biodegradable, less toxic and more environmentally friendly. In this work, 176 marine hydrocarbon-degrading bacterial isolates from petroleum-contaminated sites along the Norwegian coastline were isolated and screened for their capacity to produce biological SACs. Among them, 18 isolates were capable of reducing the surface tension of the culture medium by at least 20 mN m −1 and/or capable of maintaining more than 40% of the emulsion volume after 24 h when growing on glucose or kerosene as carbon and energy source. These isolates were members of the genera Pseudomonas, Pseudoalteromonas, Rhodococcus, Catenovulum, Cobetia, Glaciecola, Serratia, Marinomonas and Psychromonas . Two isolates, Rhodococcus sp. LF-13 and Rhodococcus sp. LF-22, reduced surface tension of culture medium by more than 40 mN m −1 when growing on kerosene, n -hexadecane or rapeseed oil. The biosurfactants were produced by resting cells of the two Rhodococcus strains suggesting the biosynthesis of the biosurfactants was not necessarily associated with their growth on hydrocarbons.